2009
DOI: 10.1136/bmj.a3147
|View full text |Cite
|
Sign up to set email alerts
|

Comparing hospital and telephone follow-up after treatment for breast cancer: randomised equivalence trial

Abstract: Objective To compare traditional hospital follow-up with telephone follow-up by specialist nurses after treatment for breast cancer. Design A two centre randomised equivalence trial in which women remained in the study for a mean of 24 months. Setting Outpatient clinics in two NHS hospital trusts in the north west of England Participants 374 women treated for breast cancer who were at low to moderate risk of recurrence. Interventions Participants were randomised to traditional hospital follow-up (consultation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
238
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(250 citation statements)
references
References 26 publications
10
238
0
2
Order By: Relevance
“…An Australian study reported that BCN's perceived themselves as important providers of psycho-social care and a link between patients and other services throughout the cancer journey; a role vital for the continuity of care (Jones, Leach, Chambers, Occhipinti 2010). In previous work it has been shown that BCN's are important sources of information and support for women who have completed their treatment, with continuity of care and building a trusting relationship shown to be important factors that patients value about contact with BCN's (Beaver, Williamson, Chalmers 2010;Beaver, Tysver-Robinson, Campbell, Twomey, Williamson, Hindley et al 2009). However, breast cancer is the most common cancer and BCNs have extremely high case loads, necessitating a focus on newly diagnosed patients who need support to cope with the cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Australian study reported that BCN's perceived themselves as important providers of psycho-social care and a link between patients and other services throughout the cancer journey; a role vital for the continuity of care (Jones, Leach, Chambers, Occhipinti 2010). In previous work it has been shown that BCN's are important sources of information and support for women who have completed their treatment, with continuity of care and building a trusting relationship shown to be important factors that patients value about contact with BCN's (Beaver, Williamson, Chalmers 2010;Beaver, Tysver-Robinson, Campbell, Twomey, Williamson, Hindley et al 2009). However, breast cancer is the most common cancer and BCNs have extremely high case loads, necessitating a focus on newly diagnosed patients who need support to cope with the cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued that surgery, cutting out the problem, is readily understood whereas systemic treatment is more complex to understand (Beaver, Jones, Susnerwala, Craven, Tomlinson, Witham et al 2005). It has been shown that breast care nurses (BCN) are an important source of information and support, helping women cope with their disease (Beaver, Tysver-Robinson, Campbell, Twomey, Williamson, Hindley et al 2009;Cruikshank, Kennedy, Lockhart, Dosser, Dallas 2008,). However, for those women who receive neo-adjuvant treatment, it is not clear what their specific needs and concerns are and how services can best be organised to meet those needs.…”
Section: Exploring Patient Experiences Of Neo-adjuvant Chemotherapy Fmentioning
confidence: 99%
“…Among patients with tumours of the central nervous system, nurse-based follow-up was found to be satisfactory and to decrease outpatient workload by 30% 19 . In a study of ebc patients with a low-tomoderate risk of recurrence, telephone follow-up by specialist nurses (consultation, with structured intervention and mammography) was as effective as traditional hospital follow-up (consultation, clinical examination, and mammography) 20 . Breast cancer nurse specialists may be particularly well-positioned to address the information and psychosocial needs of women with ebc, because those women are more likely to discuss their needs with a nurse than with a physician who is often perceived as being too busy to address such issues 21,22 .…”
Section: Nurse-based Modelmentioning
confidence: 99%
“…A systematic review on follow-up of cancer in primary versus secondary care reported weak evidence that primary care follow-up was effective [4]. Patients treated for breast and colorectal cancer have reported high levels of satisfaction with nurse-led telephone follow-up [13][14][15]. In the United Kingdom (UK), the National Cancer Survivorship Initiative (NCSI) and the more recent Living With and Beyond Cancer (LWBC) programme both advocated an individualised approach to follow-up based on risk stratification, concentrating care for those perceived to be at a greater risk of recurrent disease and for other issues that arise as a consequence of diagnosis or treatment [16].…”
Section: Routine Follow-up In Oncology Practicementioning
confidence: 99%